Mixed Taper Equations for African Mahogany Plantations ( Khaya grandifoliola C. DC.) Near Thinning and Clear-cut Ages - Ximena Mendes de Oliveira; Andressa Ribeiro; Rafaella Carvalho Mayrinck; Antonio Carlos Ferraz Filho (Floresta e Ambiente)
Abstract The present study aimed to develop taper equations for African mahogany trees in two important ages (near to thinning and near to clear-cut ages), using, respectively, 100 seven-year-old trees were scaled in Minas Gerais and 46 fourteen- and fifteen-year-old trees were scaled in Pará. The fifth-degree polynomial, the polynomials with integer and fractional powers, the Kozak exponential model, and the modified Kozak model were tested. The equations were assessed and, next, the inclusion of a random term in the best equation at tree level was tested. The best resulting equation was selected, and it was validated using the bootstrapping method. The Kozak exponential model and the modified Kozak model were selected, to trees near thinning and near clear-cut age, respectively. Inserting a random term at tree level in the equation improved its estimates by 5.2% and 8.9% for trees near thinning and clear-cut ages, respectively.